The Effect of Job Satisfaction on Performance in Institute Of Health Science Nahdlatul Ulama Tuban - mokhamad nurhadi; tiara putri ryandini (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2019)
Problems human resources should get attention was matter of performance. Performance is work performance to reach organizational goals. One factor that can influences the performance was job satisfaction that was perception workers to rewards received .The purpose of this research to know relations performance to the job satisfaction on employees in Nahdlatul Ulama Institute of health science Tuban. The research design used analytic correlation with cross sectional time approach. The population in the study were 29 employees according to the inclusion criteria, the sample was taken using simple random sampling amounted to 27 respondents. The independent variable is job satisfaction, while the dependent variable is performance. Data collection using questionnaires. Data analysis using spearman rank test with value α = 0,05.The almost entirely of employees have good performance and the most of the employees who have satisfied job satisfaction. Employees who have good performance there are many in satisfied job satisfaction. Spearman rank test results got job satisfaction variable (p<0,05) have relation to performance, with strong correlation (r=0,674) and direction of positive correlation which means more satisfied job satisfaction employee hence, its performance increases.Concluded that job satisfaction can affect employee performance. So the evaluation of work needs to be improved with several ways to improve performance by providing fair job opportunities, assessing the recruitment process appropriately, adjusting compensation and providing training and development.